Impact of Substrate Rotation on Optical, and Electrochromic Properties of wo3 Films Prepared Magnetron Sputtering for Electrochromic Applications - Radhalayam, D (Elsevier B.V., 2025)
WO3 films were prepared on fluorine-doped tin oxide (FTO) and CG glass substrates vusing sputtering. In the deposition, the substrates were rotated with different rpms 0, 1, 3, and 5 and annealed for 2 h at 400 °C. The deposited films were characterized using SEM for surface morphology, XRD for crystal structure, Uv–Vis spectrometry for optical studies, and electrochemical analysis. The SEM analysis revealed that the deposited samples were smooth. XRD analysis revealed crystalline peaks in the annealed samples, whereas the samples that were deposited by RT displayed an amorphous character. The transmittance and bandgap values varied with respect to the substrate rotation speed and annealing temperature. Chronoamperometry (CA) and cyclic voltammetry (CV) were performed in 0.5 M H2SO4. From the CV analysis, the highest cathodic peak current and diffusion coefficient values were observed for the substrate at rpm 5 because of its porous nature, and for the annealed samples, the cathodic peak current decreased. From CA analysis, the duration of coloration for all thin films was greater than the duration of bleaching time. © 2025 Elsevier B.V.